Variability and climatic changes in series of maximum air temperature and precipitation in Brasília – DF (Research, Society and Development, 2022)
The variability is one of the most popular elements of climate dynamics, the impact of this phenomenon, even within the normal range may have significant representation in human activities. The study aims to assess climate variability in Brasilia - DF, focusing on such variations as a means to understand future changes. For this work we used maximum temperature data from the air and total monthly and annual rainfall from 1980 to 2012, the Meteorological Brasilia belonging to INMET Station. As a result it can be stated that the annual maximum temperatures were increased during the period analyzed, which may cause various socioeconomic problems as well as to human health. The total annual rainfall is noted that the figures are gradually increasing, and this increase may be related to the temperature increase, which makes it has a higher evaporation and hence greater precipitation. Maximum air temperature was increased by 10.8% and the absolute minimum temperature has increased by 9.5%. Is a significant rate, but you must stay alert because this increase can come to cause various socioeconomic problems such as influence on the loss of crops, problems with thermal comfort and even higher incidence of spread of disease and folds in agriculture and in humans. In the total annual rainfall, it comes up showing a gradual increase in their rates this the 1980s, this increase may be related to the increase in temperature, which makes them have a more evaporation and thus more precipitation. An anomalous effect of the distribution of rainfall is observed during the dry spells in January. This climatic factor is known by farmers in the cerrado and cerradão region in many years and is responsible for crop failure. These variability of temperature fluctuations of the increased maximum air and increases in rainfall may be correlated with local changes (vertical growth, asphalt cover, reduced afforestation, low soil moisture, fires, and increase the vehicle fleet). The temperature of the maximum annual air showed great variation between the study period, the absolute maximum temperature was increased by 10.8% and the minimum air temperature has increased by 9.5%. Is a significant rate, but you must stay alert because this increase can come to cause various socioeconomic problems such as influence on the loss of crops, problems with thermal comfort and even higher incidence of spread of disease and folds in agriculture and in humans.